ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN PERAWAT MELAKUKAN HAND HYGIENE SESUAI SPO DIRUANG KELIMUTU DAN CEMPAKA RSUD. PROF. DR. W. Z. JOHANNES KUPANG. - Yuni Pundar (CHMK NURSING SCIENTIFIC JOURNAL, 2019)
ABSTRACT Background: Compliance was a term used to describde obedience or submissive to pre-determined goal, compliance was the extent to a person's behavior complies with the provisions given by health professionals, according to Niven in Ghana (2010). Obedience was like submissive to orders or rules. Whereas obedience was behavior according to the rules and discipline, according to Lukman Ali (1999), in Suparyono (2010). The purpose of this study was to find out the factors of the five characteristics of nurses: age, sex, level of education, years of service, knowledge that affected nurses' compliance on carrying out hand hygiene according to SPO in the Kelimutu and Cempaka room of RSUD Prof. Dr. W. Z Johannes Kupang with 39 respondents. This research used cross-sectional method study used total sampling techniques. Bivariate analysis of data processing used the Chi-Square test. The results of the study proved that only the work period factor has an influence to the nurse’s compliance with hand hygiene, which results in a P-value of 0.033 <α = 0.05. It can be concluded that the length of service can affected nurse’s compliance with hand hygiene because the longer a person works, the more experience he/she gets and the greater the responsibility and concern for personal, family and patient care. Keywords: Compliance, nurses, hand hygiene, work period.